INSTAGRAM SEBAGAI GAYA HIDUP MASYARAKAT KOTA PEKANBARU (STUDI KOMUNITAS INSTAGRAM DI KOTA PEKANBARU) - Eko Irawan; Yusmar Yusuf (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Along with the development of the current era, playing the media Instagram not just to search a popularity but as a means to work especially for children community instagram in Pekanbaru City, in addition to exchange thoughts fellow instagram users they can also share experiences in social media instagram, whatever Which they do it all because it has become a necessity for them to always play social media instagram and make lifestyle for them. The phenomenon of community lifestyle that makes social media instagram as lifestyle make the purpose of this research. In this research the subject of research is six people, those who become the subject of research is a member of community instagram of Pekanbaru city which has made social media instagram as his lifestyle. Data collection is done by observation following weekly activities from the community as well as interviews and documentation. Interviews conducted are in-depth interviews where the researcher ask questions verbally and directly with the subject in full and in depth. According to research that has been done can be concluded Pekanbaru urban society to play social media instagram has become a necessity for them, things that they can from users of social media instagram like information, add friendship make they always want to play the media.Keywords: Instagram, Lifestyle, Community